Pressure-Correction Projection FEM for Time-Dependent Natural Convection Problem (Communications in Computational Physics, 2018)
Pressure-correction projection finite element methods (FEMs) are proposedto solve nonstationary natural convection problems in this paper. The first-order andsecond-order backward difference formulas are applied for time derivative, the stabilityanalysis and error estimates of the semi-discrete schemes are presented usingenergy method. Compared with characteristic variational multiscale FEM, pressure-correctionprojection FEMs are more efficient and unconditionally energy stable. Amplenumerical results are presented to demonstrate the effectiveness of the pressure-correctionprojection FEMs for solving these problems.